The Influence of Baamboozle Learning Media on Social Studies Learning Outcomes of Grade IV Students - Pratiwi, Afifah Agustin Putri; Valen, Andri; Yuneti, Armi (Global Education Journal, 2025)
Learning process activities are formed in a planned manner, this activity can facilitate effective learning that leads to the main determinants of adequate educational success for students so that learning outcomes are carried out well. This study aims to determine the influence of baamboozle learning media on the learning outcomes of fourth-grade students of SD Negeri 60 Lubuklinggau. The research method used is a quantitative approach with experiments. The population in this study was all fourth-grade students of SD Negeri 60 Lubuklinggau and the sample was class IV.B as an experimental class taken randomly. The data collection technique was carried out using a multiple-choice test technique of 20 questions. The data analysis technique used the t-test at a significance level of α = 0.05. The results of the study showed that there was an influence of baamboozle learning media on the learning outcomes of fourth-grade students of SD Negeri 60 Lubuklinggau. The average learning outcomes of students in the experimental class were 82.91 and the control class was 69.96, analyzed using the formula for the equality test of two means (t-test) with a value (t (count)> t (table) (4.76> 1.67), that Ho was rejected and Ha was accepted. So, this study has the Effect of Baamboozle Learning Media on the Social Studies Learning Outcomes of Grade IV Students of SD Negeri 60 Lubuklinggau.